Using of Sun Power Plant to Light Out The Residential Environment of Lau Damak Village - Utomo, Budi; Dalimunthe, Afifuddin; Husni, Muhammad (Talenta Publisher, 2021)
Until now, it seems that electricity is still a challenge in Indonesia, there are still many who have not enjoyed electricity for those who live in suburban or coastal areas, and some are located not far from cities. The target area is relatively close to the center of the capital, but has escaped the attention of the government because the location is quite remote with a minimal population, so it is considered uneconomical to provide electricity to this area. This hamlet is also inhabited by less than 18 families, so that only those with an interest are left in and out of this hamlet. The remote location from one house to another makes the construction of the electricity network no longer efficient for State Electricity Company. Therefore, people must be willing to live without electricity. Lighting as a basic need must be met from an oil lamp (sentir). Some residents who have a few advantages will buy individual generators. This generator only operates from 06.30 pm to 09.00 pm. After entering the sleep time, the generator is immediately turned off, the lighting is continued using an oil lamp. The emergence of the USU Community Services Implementing Team to this partner area provided new hope for the community. The community enthusiastically complained about this condition and hoped that the USU Community Services Implementation Team could help with these residents' problems. The results of monitoring by the Community Services Implementing Team at several residents 'houses proved the residents' complaints. Electric lighting as a basic need for residents is believed to be able to be completed using existing knowledge at the university in the form of lighting using solar power. Science and Technology The USU Community Services Team through the joining program has now produced economical science and technology products and realizes the expectations of the people in this region. Now people can enjoy light for 24 hours using electricity from solar energy. The community would like to thank the team and university for the scientific products that were donated to this village.